The contribution of penguin guano to the Southern Ocean iron pool - Oleg Belyaev; Erica Sparaventi; Gabriel Navarro; Araceli Rodríguez-Romero; Antonio Tovar-Sánchez (Nature Communications, 2023)
Abstract Iron plays a crucial role in the high-nutrient, low-chlorophyll Southern Ocean regions, promoting phytoplankton growth and enhancing atmospheric carbon sequestration. In this area, iron-rich Antarctic krill (Euphausia superba) and baleen whale species, which are among their main predators, play a large role in the recycling of iron. However, penguins have received limited attention despite their representing the largest seabird biomass in the southern polar region. Here, we use breeding site guano volumes estimated from drone images, deep learning-powered penguin census, and guano chemical composition to assess the iron export to the Antarctic waters from one of the most abundant penguin species, the Chinstrap penguin (Pygoscelis antarcticus). Our results show that these seabirds are a relevant contributor to the iron remobilization pool in the Southern Ocean. With an average guano concentration of 3 mg iron g−1, we estimate that the Chinstrap penguin population is recycling 521 tonnes iron yr−1, representing the current iron contribution half of the amount these penguins were able to recycle four decades ago, as they have declined by more than 50% since then.